Qualitative evaluation of anterior segment in angle closure disease using anterior segment optical coherence tomography - Sasan Moghimi; Rebecca Chen; Nikoo Hamzeh; Nassim Khatibi; Shan C. Lin (Journal of Current Ophthalmology, 2016)
Purpose: To evaluate different mechanisms of primary angle closure (PAC) and to quantify anterior chamber (AC) parameters in different subtypes of angle closure disease using anterior segment optical coherence tomography (AS-OCT). Methods: In this prospective study, 115 eyes of 115 patients with angle closure disease were included and categorized into three groups: 1) fellow eyes of acute angle closure (AAC; 40 eyes); 2) primary angle closure glaucoma (PACG; 39 eyes); and 3) primary angle closure suspect (PACS; 36 eyes). Complete ophthalmic examination including gonioscopy, A-scan biometry, and AS-OCT were performed. Based on the AS-OCT images, 4 mechanisms of PAC including pupillary block, plateau iris configuration, thick peripheral iris roll (PIR), and exaggerated lens vault were evaluated. Angle, AC, and lens parameter variables were also evaluated among the three subtypes. Results: There was a statistically significant difference in the mechanism of angle closure among the three groups (p = 0.03). While the majority of fellow eyes of AAC and of PACS eyes had pupillary block mechanism (77.5% and 75%, respectively), only 48.7% of PACG eyes had dominant pupillary block mechanism (p = 0.03). The percentage of exaggerated lens vault and plateau iris mechanisms was higher in PACG eyes (25.5% and 15.4%, respectively). Fellow eyes of AAC had the shallowest AC (p = 0.01), greater iris curvature (p = 0.01), and lens vault (p = 0.02) than PACS and PACG eyes. Iris thickness was not significantly different among the three groups (p = 0.45). Conclusion: Using AS-OCT, we found that there was a statistically significant difference in the underlying PAC mechanisms and quantitative AC parameters among the three subtypes of angle closure disease.